Sbaihia site sets a model for agrosilvopastoral practices - Louhaichi, Mounir (Food and Agriculture Organization of the United Nations, 2024)
During the FAO Global Conference on Sustainable Livestock Transformation, held at FAO Headquarters in Rome, Italy, from September 25 to 27, 2023, twelve success stories of sustainable livestock transformation were showcased. The conference theme, "Better Production, Better Nutrition, Better Environment, Better Life," highlighted innovative approaches to enhancing livestock practices. Mounir Louhaichi presented Tunisia's successful case study: ,Sbaihia site sets a model for agrosilvopastoral practices, demonstrating the effective strategies implemented in the region.